Dynamic Management of Sustainable Development Methods for Large Technical Systems - Krishans, Zigurds; Mutule, Anna.; Merkuryev, Yuri.; Oleinikova, Irina; SpringerLink (Online service) (London : Springer London, 2011)
Dynamic management of systems development is a precondition for the realization of sustainable system development. This approach allows for the usage of systems theory methods that take into consideration the interaction of decisions made over time and space. A characteristic feature of this kind of method is that the process of sophisticated object development over time is examined for optimal decision selection. This requires the application of modelling methods that represent properties of the developing objects, high speed calculation methods for the estimation of technical and economic characteristics, as well as effective optimization methods. Dynamic Management of Sustainable Development presents a concise summary of the authors$1 (Bresearch in the area of dynamic methods analysis of technical systems development. Along with systematic illustration of mathematical methods, considerable attention is drawn to practical realization and applications. Dynamic Management of Sustainable Development will be helpful for scientists involved in the mathematical modelling of large technical systems development and for engineers working in the area of large technical systems planning.s
1. Problem Statement -- 2. Mathematical Basics of LTS Sustainable Development Dynamic Management -- 3. Modelling LTS D-process -- 4. LTS D-process Dynamic Optimization on All D-states -- 5. Optimal Initial States (OIS) Method -- 6. Optimal Initial States Searching Methods -- 7. LTS Sustainable Development Management Approximate Methods -- 8. Information Technology for Sustainable Development of Electric Power Systems -- 9. The Database -- 10. Software System for Sustainable Development Management.
Keywords: Engineering; Software engineering; Renewable energy sources; Sustainable development; Technology; Engineering; Renewable and Green Energy; Mathematical Modeling and Industrial Mathematics; Special Purpose and Application-Based Systems; Sustainable Development; Renewable and Green Energy; Technology Management